Intimate partner violence help-seeking norms: scale reliability and cross-sectional multilevel associations with intimate partner violence among youth in Nairobi, Kenya - Peter Gichangi; Mary Thiongo; Anaise Williams; Bianca Devoto; Shannon N. Wood; G Wamue-Ngare; Kristin G. Bevilacqua; Michele R. Decker (BMJ Open)
Objectives Intimate partner violence (IPV) threatens women’s health and safety. Support services can mitigate the impact, yet few survivors seek services in part due to social norms that discourage use. Little agreement exists on how to measure norms and attitudes related to IPV help-seeking. The objectives were to (1) refine an IPV Help-Seeking Attitudes Scale and examine its psychometric properties, (2) explore differences in attitudes between young men and young women, and (3) examine associations of past 6-month IPV among young women with the scale at the individual level (individual attitudes) and the by-gender community-aggregated averages (community norms) among youth in Nairobi, Kenya.Design This cross-sectional, secondary analysis used data from a phone-based survey with a cohort of young men and young women recruited via respondent-driven sampling from April to May 2021. Cross-sectional exploratory factor analysis assessed underlying latent constructs. Multilevel mixed-effects models assessed associations with IPV experience for young women.Setting and participants A youth cohort of 586 men and 591 women aged 15–24 years in Nairobi, Kenya.Primary outcome measure Past 6-month physical and/or sexual IPV among young women.Results The IPV Help-Seeking Attitudes Scale had acceptable internal reliability (Cronbach’s alpha >0.60). IPV prevalence was 17.5%, among whom 21.7% had sought any help for the past 6-month IPV. A one-unit increase in the community aggregate IPV Help-Seeking Attitudes Scale among young women was associated with reduced odds of IPV (aOR: 0.17, 95% CI: 0.03–0.98). However, the individual-level attitudes scale was not associated with IPV nor was the men’s community aggregate scale.Conclusions The IPV Help-Seeking Attitudes Scale had adequate psychometric properties. The results suggest that young women living in a community where the norm among women enables IPV response may have a reduced risk of IPV. Community norms change to better enable IPV response among young people may help reduce IPV and increase help-seeking.